The effects the Preschool life skills program has on children’s social skills - Steinunn Agnarsdóttir 2000- (2022)
Children who have a hard time acquiring social skills at a young age are more likely to have trouble with social and academic skills in the future. Research has demonstrated increasing effects on children’s social skills using the Preschool life skills program (PLS). PLS is a class-wide teaching program that aims to teach children appropriate social skills by having teachers make opportunities to teach appropriate behavioral skills. The present study aimed to add to the existing literature on the PLS program by examining the effectiveness of unit 1 of the PLS program on social skills, precisely following instructions, among kindergarten children in Iceland and adding a control group that didn’t go through PLS. Participants were 18 children in the test group and 16 in the control group aged 4-6 years old. Measurements were conducted before and after the PLS program was implemented by recording correct responses to instructions and what instructions were given. Results demonstrated that the test group did not improve more in instruction following than the control group. However, when dividing the instructions into children following individual instructions, all children follow group instructions, and some children follow group instructions; a difference in groups can be found in all cases, but not all results were significant. Keywords: PLS program, social skills, kindergarten, instruction following Börn sem eiga erfitt með að tileinka sér félagsfærni á yngri árum eru líklegri til að eiga í erfiðleikum með félagslega og akademíska færni í framtíðinni. Rannsóknir hafa sýnt fram á aukningu í félagsfærni hjá börnum með því að nota Preschool life skills program (PLS). PLS er kennslutækni sem miðar að því að kenna börnum viðeigandi félagsfærni með því að láta kennara búa til tækifæri til að kenna viðeigandi félagsfærni. Þessi rannsókn miðar að því að bæta við fyrirliggjandi þekkingu um PLS með því að skoða áhrif fyrsta hluta PLS á félagsfærni, þá að fylgja fyrirmælum, meðal leikskólabarna á Íslandi og að bæta við ...